The relationship between non-financial rewards and job satisfaction among support staff at Sarawak Skills Development Centre (SSDC)/ Ruhil Izzati Rushdi - Rushdi, Ruhil Izzati (2018)
This research paper is conducted on the title of The Relationship between Non- financial Rewards and Job Satisfaction among the support staff in Sarawak Skills Development Centre (SSDC). This study was done to measure the level of satisfaction among the 81 support staff at SSDC on their acceptance of non-financial rewards. The current research is to explore non-financial rewards affect the level of job satisfaction in Sarawak Skills Development Centre (SSDC). Non-financial rewards are precisely focused on Job Enrichment and Employees’ Recognition as the independent variables with the dependent variable, Job Satisfaction. The research was done by including all the support staff in SSDC as participants who answered the questionnaires that were distributed to them. The findings revealed that Employees’ Recognition and Job Enrichment have positive relationship with Job Satisfaction, r=0.317 and r=0.394 respectively because SSDC always reward their employees for instance, the best support staff award and the best instructor award. There were 81 questionnaires were collected with total of 81% or survey rate responses. In conclusion, non-financial rewards affected their level of Job Satisfaction among the support staff at Sarawak Skills Development Centre (SSDC). For future research improvement, researcher are recommended to distribute the questionnaire to the public sector in order to measure their level of job satisfaction towards non-financial rewards and enlarge the scope of non-financial rewards.